American gun : a history of the U.S. in ten firearms - Kyle, Chris, 1974-2013 (William Morrow, 2013)
In "American Gun", the deadliest sniper in U.S. history tracks down and shoots the most important American firearms, from a flintlock rifle to a Colt revolver to the latest high-tech weapon he used as a SEAL. Chris Kyle uses these guns as a window on United States history, making the sweeping argument that the American story has been tied to and shaped by the gun.